Upaya Meningkatan Prestasi Belajar Siswa dengan Metode Make A Match pada Mata Pelajaran Ilmu Pengetahuan Sosial di Kelas IX-C SMP Negeri 4 Praya - Edi Supardi (Jurnal Kependidikan: Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran dan Pembelajaran, 2019)
The purpose of this research was to improve the students learning achievement of Social Sciences (IPS) in class IX-C of SMP Negeri 4 Praya by using Make A-Match learning method. This research used classroom action research methods and was carried out at the fourth class of IX-C in the even semester of the academic year 2018/2019 with 39 students, in which 16 male students and 23 female students. The sequence of research activities included: (1) Planning, (2) Implementation of actions, (3) Observation, (4) Reflection. The result of the study showed that Make-a Match method was proven to improve the students learning achievement as seen in the result of recapitulation of each cycle from the first cycle, in which 26 students or 65% were said to be complete and 13 students or 33% were not complete, and in the second cycle 37 students or 92.31% were said to be complete and 3 students or 7.69% had not been complete. From the recapitulation result of each cycle above, it was seen that cycle I to cycle II increased by 4.57%. Thus, it can be concluded that the use of Make-a Match learning method can improve the students learning achievement of Social Sciences (IPS) in class IX-C of SMP Negeri 4 Praya in the year of 2018/2019.